2019
DOI: 10.2147/ijn.s202457
|View full text |Cite
|
Sign up to set email alerts
|

<p>3D printed zirconia ceramic hip joint with precise structure and broad-spectrum antibacterial properties</p>

Abstract: Background: Nowadays, zirconia ceramic implants are widely used as a kind of hip prosthesis material because of their excellent biocompatibility and long-term wear resistance. However, the hip joint is one of the major joints with complex 3D morphological structure and greatly individual differences, which usually causes great material waste during the process of surgical selection of prosthesis. Methods: In this paper, by combining ceramic 3D printing technology with antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…Currently, knee and hip arthroplasty are taking up an increasing proportion of orthopedic surgery, and the demand especially from those patients mainly over 60 years old will continue to grow [ 1 , 2 ]. Evidence has indicated that postoperative delirium (POD) is a relatively common and serious complication in patients undergoing hip and knee arthroplasty, and the probability of occurrence is up to 17.6% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, knee and hip arthroplasty are taking up an increasing proportion of orthopedic surgery, and the demand especially from those patients mainly over 60 years old will continue to grow [ 1 , 2 ]. Evidence has indicated that postoperative delirium (POD) is a relatively common and serious complication in patients undergoing hip and knee arthroplasty, and the probability of occurrence is up to 17.6% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prosthesis with a better antibacterial effect can decrease the time of operation and joint function recovery in patients by reducing the trauma suffered by the patient. Yang et al [ 58 ]recently combined 3D printing with antimicrobial nano-modification technology to obtain zirconia ceramic implant materials with a precise 3D structure and long-term wear resistance. The prepared hip prosthesis precisely matched the affected part with good biocompatibility and sterilization ( Figure 5 ).…”
Section: Periprosthetic Hip Joint Infectionmentioning
confidence: 99%
“…Particularly, an yttria-stabilized zirconia demonstrates excellent fracture resistance and flexural strength. Due to its superior mechanical properties, zirconia has been used as ball head for total hip replacements [8][9][10]. In addition, it possesses an excellent aesthetic effect with almost the same color as the teeth [11,12].…”
Section: Introductionmentioning
confidence: 99%